Possibilidades de integração curricular no contexto de implementação do novo ensino médio no Rio Grande do Sul - Garcia, Carolina Neugebauer (Universidade do Vale do Rio dos Sinos, 2025)
The research presents an analysis of the possibilities and challenges of curricular integration in the context of the implementation of the New High School in the state education system of Rio Grande do Sul. It stems from the issue related to the tensions between the legal discourse of integration and school practices, questioning to what extent curricular integration is effectively implemented as a formative proposal in public schools in light of the guidelines of the High School reform. The objective is to understand how school subjects perceive, interpret, and operationalize curricular integration, considering the material, pedagogical, and political conditions in which they are inserted. A qualitative approach is adopted, with a case study conducted in a state school in the municipality of Sapucaia do Sul. The methodological procedures include document analysis, semi-structured interviews with administrators, teachers, and students, as well as observation of pedagogical planning processes. The research is based on theoretical frameworks from the field of critical curriculum, especially the contributions of James Beane, Jurjo Torres Santomé, Alice Casimiro Lopes, and Roberto Rafael Dias da Silva, articulated with the critique of neoliberal policies in education. The results show that, although there is a discourse that values integration, school practices remain strongly conditioned by the disciplinary logic, the lack of time for collective planning, the absence of continuing education, and the contradictions present in the normative documents themselves. It concludes that the implementation of curricular integration depends not only on the adherence of school subjects, but fundamentally on structural conditions, coherent public policies, and a collective movement capable of challenging the logic of flexibility imposed by the market, reaffirming the social role of the school in critical and emancipatory education.
Keywords: Integração curricular; Novo Ensino Médio; Currículo; Política educacional; Ensino Médio – Rio Grande do Sul; Curricular integration; New High School; Curriculum; Educational policy; High School – Rio Grande do Sul; ACCNPQ::Ciências Humanas::Educação